Assessing children's swallowing: parent and professional perceptions. Issue 3 (4th July 2016) - Cockerill, Helen; van den Engel - Hoek, Lenie; Harding, Celia
Abstract : Purpose: – For infants and children who have difficulties with eating, drinking and swallowing (dysphagia), there are significant health risks that include aspiration (food and fluid entering the lungs) and poor growth. Videofluoroscopy is often the instrumental method of assessment used to exclude or confirm aspiration. The purpose of this paper is to investigate parental and referrer perceptions of the reasons for and the outcomes of videofluoroscopy. Design/methodology/approach: – Data were gathered through the use of structured telephone interviews before and after videofluoroscopy. Findings: – Four key themes emerged: first, the importance of identifying specifically the problems with swallowing; second, understanding the rationale for videofluoroscopy; third, preparing a child for videofluoroscopy; and fourth, using videofluoroscopy to inform management. Referrers used videofluoroscopy to confirm their concerns about a child's ability to swallow safely. Practical implications: – Parents understood that the purpose of videofluoroscopy was to identify specific swallowing difficulties. They reported anxieties with managing the child's positioning during the procedure and whether the child would eat. They also had concerns about outcomes from the study. Some of these issues raise questions about the true value and benefits of videofluoroscopy. Originality/value: – This is the first study that considers parent views of an instrumental assessment. For some parents of children with learning disabilities, mealtimes are an important social occasion. Further studies that focus on decision making about children with learning disabilities who find feeding difficult are warranted as parents feel loss and disempowerment when decisions are made about non-oral feeding.